EFFORTS TO IMPROVE LEARNING MOTIVATION OF GRADE VIII STUDENTS IN THE SUBJECT OF MATHEMATICS USING THE PAKEMSTRATEGY - Fatahilah, Achmad; Achmad, Ridho; Jaeng, Sulaiman; Makhrus Ali, M. (International Journal of Multidisciplinary Reseach, 2025)
The purpose of he did study This is For know presentation amount students who have reach success in increase motivation Study mathematics and knowing efforts made by mathematics teachers For increase motivation his students to lesson mathematics with using the Pakemstrategy in Class VIII A of Riyadlus Islamic Middle School sholihin. Research that has been done This is study action class (PTK) and techniques used in the research is technique quantitative and descriptive qualitative research data obtained from results interviews, observations, recording field and documentation. Based on results from study can concluded that study This done with 2 cycles. And the results cycle 1, namely there is presentation student as much as 38.3% of amount students, who are active in activity learning mathematics. while in cycle 2 there is result 89.8% of amount students, who are active in learning mathematics. Happened improvement percentage in cycle 2, meaning amount enthusiastic students​ to lesson mathematics the more many. Can withdrawn conclusion that motivation student the more increasing. Increasing motivation carried out by teachers is results application of Pakemlearning strategies. Teachers' action efforts in implementing Pakem, including : creating pleasant atmosphere, giving rewards, teachers are open, teachers must active and teachers must discipline.